Parasites of Cockroach Periplaneta americana (L.) in Al-Diwaniya province,Iraq. - S. Mahdi Al-Yaqoobi, Muhammed; M. Hamza Al-Mayali, Hadi (University of Thi-Qar Journal of Science, 2019)
Out of 150 cockroaches examined in this study, 125 cockroaches (83. 33%) were infectedwith one or several species of external parasites (33.3) or gastro-intestinal helminthes (80%). Thepercentage infection and number of parasites of Cockroaches trapped in the toilets of houses morethan infection of cockroaches trapped from the kitchens of houses (100% and 50%respectively)and 2-62 parasites/ml of Cockroaches trapped in the toilets while those trapped from the kitchenswas1- 28 parasites/ml houses.A seven species were isolated from the external surface and intestinal tract represented twoprotozoa and five nematodes. This species were:Entamoeba blatti (33%), Nyctotherus ovalis (65.3 %), Hammersmiditiella diesingi (33.3 %),Thelastoma bulhoe (51.4 %), Gordius robustus (Horsehair worm) (1.3%), Enterobiusvermicularis eggs , (2%) Ascaris lumbricoids eggs (1.3%). No Cestodes were records in thestudy.Prevalence of intestinal worms was statistically higher significant than the protozoa in (P<0.05).The number of worms per cockroaches ranged from 1-3 while protozoa 42 parasites/ml.Prevalence of endoparasites were higher than ectoparasites and intestinal worms was statisticallyhigher significant than the protozoa in (80%; 3. 3%) and (83. 3%; 65.3 %) respectively.This study revealed Cockroach represent an important reservoir or carrier for medical importanceparasites of human in houses as Enterobius vermicularis and Ascaris lumbricoids .The work presents the first record of cockroach's parasites in Al-Diwaniya.